1. Question:উৎপাদকে বিশ্লেষণ কর: `4a^2 - 12ab + 9b^2 - 4c^2` 

    Answer
    `4a^2 - 12ab + 9b^2 -4c^2`
    
     `= (2a)^2 - 2.2a.3b + (3b)^2 - 4c^2`
    
     `= (2a - 3b)^2 - (2c)^2`
    
     `= (2a - 3b + 2c) (2a - 3b - 2c)`   (Ans)






    1. Report
  2. Question:উৎপাদকে বিশ্লেষণ কর: `9x^4 - 45a^2x^2 + 36a^4` 

    Answer
    `9x^4 - 45a^2x^2 + 36a^4`
    
     `= 9(x^4 - 5a^2x^2 + 4a^2)`
    
     `= 9(x^4 - 4a^2x^2 - a^2x^2 + 4a^4)`
    
     `= 9{x^2(x^2 - 4a^2) - a^2(x^2 - 4a^2)}`
    
     `= 9(x^2 - a^2) (x^2 - 4a^2)`
    
     `= 9(x^2 - a^2){x^2 - (2a)^2}`
    
     `= 9(x + a) (x - a) (x + 2a) (x - 2a)`  (Ans)






    1. Report
  3. Question:উৎপাদকে বিশ্লেষণ কর: `a^2 + 6a + 8 - y^2 + 2y` 

    Answer
    `a^2 + 6a + 8 - y^2 + 2y`
    
          `= a^2 + 4a + 2a + 8 - y^2 + 2y`
    
         `= a(a + 4) +  2(a + 4) - y^2 + 2y`
    
         `= (a + 4) (a + 2) + 2y - y^2`
    
       ধরি, a + b = p
    
             a + 2 = q
             ------------
                    2 = p - q  [বিয়োগ করে]
    
           :. p - q = 2
    
       এখন, `(a + 4) (a + 2) + 2y - y^2`
    
           `= pq + (p - q) y - y^2`
    
                      [:. a + 4 = p, a + 2 = q  এবং 2 = p - q]
    
           `= pq + py - qy - y^2`
    
           `= p(q + y) - y(q + y)`
    
           `= (q + y) (p - y)`
    
           `= (a + 2 + y) (a + 4 - y)`  [p, q]
    
           `= (a + y + 2) (a - y + 4)`  (Ans)
    
    
      বিকল্প সমাধান:   
          `a^2 + 6a + 8 - y^2 + 2y`
    
        `= a^2 + 6a + 9 - y^2 + 2y - 1`
    
        `= a^2 + 6a + 9 - (y^2 - 2y + 1)`
    
        `= {(a)^2 + 2.a.3 + (3)^2} - {(y)^2 - 2.y.1 + (1)^2}`
    
        `= (a + 3)^2 - (y - 1)^2`
    
        `= (a + 3 + y - 1) (a + 3 - y + 1)`
    
        `= (a + y + 2) (a - y + 4)`  (Ans)






    1. Report
  4. Question:উৎপাদকে বিশ্লেষণ কর: `16x^2 - 25y^2 - 8xz + 10yz` 

    Answer
    `16x^2 - 25y^2 - 8xz + 10yz`
    
          `= (4x)^2 - (5y)^2 - 2z(4x - 5y)`
    
          `= (4x + 5y) (4x - 5y) - 2z(4x - 5y)`
    
          `= (4x - 5y) (4x + 5y - 2z)`   (Ans)






    1. Report
  5. Question:উৎপাদকে বিশ্লেষণ কর: `2b^2c^2 + 2c^2a^2 + 2a^2b^2 - a^4 - b^4 - c^4` 

    Answer
    `2b^2c^2 + 2c^2a^2 + 2a^2b^2 - a^4 - b^4 - c^4`
    
       `= 4a^2b^2 - a^4 - b^4 - c^4 - 2a^2b^2 + 2b^2c^2 + 2c^2a^2`
    
       `= 4a^2b^2 - (a^4 + b^4 + c^4 + 2a^2b^2 - 2b^2c^2 - 2c^2a^2)`
    
       `= 4a^2b^2 - {(a^2)^2 + (b^2)^2 + (-c^2)^2 + 2a^2b^2 + 2b^2`
    
                                             `(-c^2) + (-c^2)a^2}`
    
        `= (2ab)^2 - (a^2 + b^2 - c^2)^2`
    
        `= (2ab + a^2 + b^2 - c^2) (2ab - a^2 - b^2 + c^2)`
    
        `= {(a^2 + 2ab + b^2) - c^2} {c^2 - (a^2 - 2ab + b^2)}`
    
        `= {(a + b)^2 - c^2} {c^2 - (a - b)^2}`
    
        `= (a + b + c) (a + b - c) (c + a - b) (c - a + b)`
    
        `= (a + b + c) (a + b - c) (b + c - a) (c + a - b)`
    
        `= (a + b + c) (b + c - a) (c + a - b) (a + b - c)`  (Ans)






    1. Report
Copyright © 2025. Powered by Intellect Software Ltd